THE EFFECT OF SHARE RETURN, STOCK RISK, STOCK PRICE AND TRADE VOLUME OF BID-ASK SPREAD (Study of Companies Listed in Jakarta Islamic Index (JII) for 2012-2014 Period) - Novyasari Suchi Hendryati; Sri Mulyati; Indah Umiyati (STIESA Press, 2019)
This study aims to determine the impact of stock returns, stock risk, stock price and trading volume of the bid-ask spread.This study was performed on companies listed in the Jakarta Islamic Index (JII) during the years 2012 to 2014. Sampling premises of population conducted by purposive sampling method. Samples according to the criteria that as many as 78 companies . The statistical tool used in this study is Eviews 8.1. The results found in this study that by simultan return stock, stock risk, stock price and trading volume significantly influence the bid-ask spread. Partially only variable stock returns and stock prices which have a significant influence on the bid-ask spread. While the risk of stock and trading volume have no influence on the bid-ask spread.